RELATIONSHIP BETWEEN DURATION OF TYPE 2 DIABETES MELLITUS AND BLOOD PRESSURE IN PATIENTS AT THE PERSADIA TULUNGAGUNG CLINIC - ISLAMY, AESTHETICA; Sukanto, Sukanto; Farida, Farida (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a chronic condition characterized by the body's inability to use insulin effectively. Prolonged duration of T2DM and poor glycemic control may lead to various complications, including macroangiopathy—damage to large blood vessels—which can affect blood pressure. This study aimed to investigate the relationship between the duration of type 2 diabetes mellitus (T2DM) and blood pressure levels in patients with type 2 diabetes. Methods: This study employed an analytical design with a cross-sectional approach, involving 30 respondents selected through purposive sampling. The study was conducted from June 15 to 22, 2019. Data collection involved the use of validated questionnaires and medical records, as well as direct blood pressure measurements. The Spearman Rho correlation test was used with a 95% confidence level. Results: Among the 13 respondents with a longer duration of T2DM, all (100%) had high blood pressure. The Spearman Rho test yielded a p-value of 0.000, which is less than the significance level of 0.05, indicating a statistically significant relationship. The correlation coefficient was 0.797, suggesting a strong positive correlation between the duration of diabetes and blood pressure. Conclusion: There is a significant relationship between the duration of type 2 diabetes mellitus and blood pressure levels in patients at the Indonesian Diabetes Association (PERSADIA) Clinic in Tulungagung